2014
DOI: 10.1590/abd1806-4841.20142875
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases reported by workers from UNESP campus at Rubião Jr, Botucatu-SP (Brazil)

Abstract: There are few populational studies to estimate the dimension of dermatological diseases. We performed a survey with 515 employees from UNESP campus, Botucatu (SP), exploring demographic data, medical appointments and dermatological diagnoses. Additionally, we induced questions about prevalent diseases. Appointments to the dermatologist were reported by 77% of subjects. The main dermatoses spontaneously reported were mycoses, allergies, nevi and viral warts. There were association of juvenile acne and males (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
1
14
0
2
Order By: Relevance
“…In Mexico, a multicentre survey with 50,000 individuals estimated the prevalence to be 0.21% (Estrada Castañón et al, 1992), but data for South America are relatively sparse. A small Brazilian study revealed self-reported vitiligo in one case among 515 adult workers (Ishiy, Silva, Penha, Handel, & Miot, 2014), and an examination of 9,955 schoolchildren from Amazonia resulted in a prevalence of 0.04% (Bechelli et al, 1981). It is important to note, however, that prevalence data do not only depend on study population but also on study methodology.…”
Section: Prevalence Of Vitiligo In Brazil-a Population Surveymentioning
confidence: 99%
“…In Mexico, a multicentre survey with 50,000 individuals estimated the prevalence to be 0.21% (Estrada Castañón et al, 1992), but data for South America are relatively sparse. A small Brazilian study revealed self-reported vitiligo in one case among 515 adult workers (Ishiy, Silva, Penha, Handel, & Miot, 2014), and an examination of 9,955 schoolchildren from Amazonia resulted in a prevalence of 0.04% (Bechelli et al, 1981). It is important to note, however, that prevalence data do not only depend on study population but also on study methodology.…”
Section: Prevalence Of Vitiligo In Brazil-a Population Surveymentioning
confidence: 99%
“…A telephone survey performed in Spain in 2014 reported a prevalence of 2.3%, and a small study performed in a Brazilian university campus revealed psoriasis in 1.2% of adult workers . To date, data on psoriasis population prevalence in Brazil or Latin America is lacking.…”
Section: Main Demographic Data and Prevalence Of Psoriasis According mentioning
confidence: 99%
“…This population‐based survey also explored different age groups . The chronic nature of the disease, and the high possibility that the correct diagnosis be established after time, are elements which inflate disease prevalence above the fifth decade.…”
Section: Main Demographic Data and Prevalence Of Psoriasis According mentioning
confidence: 99%
“…In the United States, 5–6 million women are thought to be affected by melasma . In a study conducted in Brazil, 15–35% of adult women were found to be affected by melasma . There are no studies documenting the exact prevalence of melasma in India.…”
Section: Introductionmentioning
confidence: 99%